Pengaruh Penyaluran Komoditas Jagung Terhadap Farmer’s Share Dan Keuntungan Hasil Usaha Tani Di Kabupaten Pamekasan - Selvia Kamilia Fitri; Muh Syarif (Journal Of Business, Finance, and Economics (JBFE), 2023)
Corn is one of the agricultural products of high value, a strong economy with growth potential. Although corn in Indonesia is the second most important food product after rice / rice. Marketing channels are the routes traveled by agricultural products when products move from farm gates, i.e. farmers, producers, to users or last users. The type of data obtained in the study consists of primary data and secondary data, primary data is data obtained directly from research respondents at the research location. In this study, primary data was obtained from corn farming in the form of primary data in the form of information about corn land area, corn cultivation. The harvest, the selling price and purchase price, and the marketing agency used. Primary data collection is carried out by means of Interviews, Observations, Documentation.